Efektifitas Rapid Sand Filter Untuk Meningkatkan Kualitas Air Daerah Gambut Di Provinsi Riau - Muhammad Nur Fajri; Yohanna Lilis Handayani; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Water is very important for human life. The human need water used for drinking, cooking, bathing, washing and any others. Therefore, the condition of clean water must have specialrequirements so that the water does not pose a problem for humans. In the area of peat particularly Riau Province, the water should be treated before consumed. One of thealternative wells water treatment peat area in Riau Province with a simple concept and experiencing such as rapid sand filter technology. This research aimed to determine the time of rapid sand filter media in improving the water quality in the area of peat in Riau province, and get the highest quality of wells water based on the pH parameters, manganese, and organic substances. Rapid sand filter media was made from PVC with 6 '' pipe diameter and145 cm of height. The results showed that rapid sand filter produced the best efficiency to raise the pH by 31.21%, lower organic content of 83.53%, and stabilized the manganesecontent by 66.67%. In general, the processing of rapid sand filter has not been able to fix the pH parameters, and organic matter in accordance with the requirement Regulation from theMinister of Health No.416/Menkes/PER/IX/1990 on water wells peat areas. The average time saturated media operation rapid sand filters is 35 calendar days.Keywords : Peat Water, Rapid Sand Filter, pH, KMnO4, Mn, media saturated age